A hole in the heart - Haghi, Dariusch; Süselbeck, Tim; Papavassiliu, Theano (European journal of echocardiography, 2010)
We present the case of a 91-year-old male whose percutaneous aortic valve replacement was complicated by perforation of the left ventricular (LV) apex caused by an extra-stiff guidewire. Although two-dimensional echocardiography was able to demonstrate a small hole at the LV apex and the presence of an LV pseudo-aneurysm, the exact size and shape of the hole could not be readily appreciated. Thus, three-dimensional (3D) echocardiography was performed and an oval-shaped hole of roughly 0.8 cm 2 could be clearly visualized. This case illustrates the unique value of 3D echocardiography in visualizing geometry and flow across LV rupture sites.
Published: 10 March 200
Gesehen am 03.03.2023